2019
DOI: 10.1194/jlr.m093096
|View full text |Cite
|
Sign up to set email alerts
|

Effects of diet and hyperlipidemia on levels and distribution of circulating lysophosphatidic acid

Abstract: Supplementary key words cholesterol • lipoprotein • low density lipoprotein • autotaxin • mass spectrometryLysophosphatidic acids (LPAs) are a class of small receptor active phospholipid signaling molecules that promote the growth, survival, and motility of many cell types. LPA, its receptors and enzymes involved in LPA generation and inactivation are implicated in many pathologies including cardiovascular, pulmonary, and neurological diseases, and cancer (1-3). These observations underscore the importance of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 54 publications
(58 reference statements)
0
19
0
Order By: Relevance
“…The extracellular LPA pool comprises distinct molecular species that differ in their acyl chain composition and binding affinity for individual LPA receptors (Yung et al, 2014). We measured LPA species in media from melanoma cells conditioned at 0, 24 and 48 hrs using LC-MS/MS (Kraemer et al, 2019) ( Figure 3A ). LPA(12:0), (16:0), (18:0), (18:1) and (20:4) were the predominant species in media containing 0.5% serum ( Figure 3B) .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The extracellular LPA pool comprises distinct molecular species that differ in their acyl chain composition and binding affinity for individual LPA receptors (Yung et al, 2014). We measured LPA species in media from melanoma cells conditioned at 0, 24 and 48 hrs using LC-MS/MS (Kraemer et al, 2019) ( Figure 3A ). LPA(12:0), (16:0), (18:0), (18:1) and (20:4) were the predominant species in media containing 0.5% serum ( Figure 3B) .…”
Section: Resultsmentioning
confidence: 99%
“…LPA exists as distinct molecular species that differ in their acyl chain composition and binding affinity for individual LPA receptors (Yung et al, 2014). We measured LPA species in the respective media from melanoma cells conditioned at 0, 24 and 48 hrs by using LC-MS/MS (Kraemer et al, 2019). As shown in Fig.…”
Section: Depletion Of Lpa By Melanoma Cells Reveals Atx As An Lpa-promentioning
confidence: 99%
“…In addition to nociceptive pain and peripheral sensitization, evidence for neuropathic components is increasing, and it has also been reported that neuropathic pain in the hip and knee OA can be up to 23% [ 28 ]. Hypercholesterolemia increases the level of total plasma lysophosphatidic acid (LPA) [ 29 ], and an animal study by McDougall et al suggested that LPA may lead to neuropathic joint pain by causing demyelination and nerve damage [ 30 ]. Although the exact mechanism in humans is not yet well understood, it is thought that these various factors are working in combination.…”
Section: Discussionmentioning
confidence: 99%
“…The plasma samples were stored at −80 • C until analysis. LPA measurements were carried out as described earlier (43). Briefly, lipids were extracted from plasma using acidified organic solvents.…”
Section: Lpa Measurementsmentioning
confidence: 99%